E-COMMERCE PRODUCTIVITY PARADOX EVIDENCE FROM THE HUNGARIAN RETAIL SECTOR - Aranyossy, Marta (European Scientific Journal, ESJ, 2013)
﻿Drastic increase in information technology investments and no growth in productivity and profitability – this was the famous “IT productivity paradox” of the 1980’s and 1990’s. B2C e-commerce systems, as mature, wide-spread and directly observable components of the corporate IT portfolio, are the perfect research subjects to further clarify the question of IT productivity in the new millennia. Are e-commerce resources associated with enhanced company competitiveness, productivity or financial performance? With routes in the resource based view, we analyzed the e-commerce capabilities of 187 Hungarian ICT retailer, explored the relationship between e-capabilities and corporate performance metrics with multivariate statistical methods. We found that online transactional capability has indeed a significant positive effect on Hungarian retail labor efficiency, the productivity paradox is dissolved. While online interactive capabilities have significant positive effect on bottom-line profitability, and a lagged positive effect on revenue growth; we could also find informational e-capabilities associated with inferior profitability.